2013
DOI: 10.1007/s00705-013-1619-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of porcine enteric caliciviruses and first detection of porcine kobuviruses in US swine

Abstract: The prevalence of porcine sapoviruses (SaVs) and noroviruses (NoVs) in nursing piglets on three pig farms in Ohio was studied. Fecal samples (n = 139) were collected from individual pigs and screened for caliciviruses by RT-PCR. Phylogenetic analysis was conducted using partial sequences of the RNA polymerase region. Three different SaV genogroups, including a newly emerging one (DO19 Korea-like) were detected. No NoVs were detected. Kobuviruses, emerging members of the family Picornaviridae, were detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
(45 reference statements)
1
23
1
Order By: Relevance
“…In addition, similar sapovirus strains were detected from gastroenteritis patients, wastewater, and oysters, which were collected from geographically related areas in the same season (241). In contrast, sapoviruses genetically indistinguishable from those detected in human clinical specimens have not been discovered in other animals (i.e., swine, mink, bats, dogs, and sea lions) (48,88,123,172,173,(249)(250)(251)(252)(253). Based on complete VP1 sequences, GV.3 porcine sapoviruses are closest to human strains; however, they can be clearly separated into a different genotype (Fig.…”
Section: Sapoviruses In Seafood Environmental Water and Animalsmentioning
confidence: 88%
“…In addition, similar sapovirus strains were detected from gastroenteritis patients, wastewater, and oysters, which were collected from geographically related areas in the same season (241). In contrast, sapoviruses genetically indistinguishable from those detected in human clinical specimens have not been discovered in other animals (i.e., swine, mink, bats, dogs, and sea lions) (48,88,123,172,173,(249)(250)(251)(252)(253). Based on complete VP1 sequences, GV.3 porcine sapoviruses are closest to human strains; however, they can be clearly separated into a different genotype (Fig.…”
Section: Sapoviruses In Seafood Environmental Water and Animalsmentioning
confidence: 88%
“…The species Aichivirus C consists of a single type, PKV-1. The existence of PKV-1 in pigs has been well documented in different countries worldwide (Amimo et al, 2014;Barry et al, 2011;Chen et al, 2013;Di Bartolo et al, 2015;Fan et al, 2013;Khamrin et al, 2009Khamrin et al, , 2010Okitsu et al, 2012;Park et al, 2010;Reuter et al, 2013;Sisay et al, 2013); however, in Vietnam, PKV-1 has only been reported from river water (Inaba et al, 2014).…”
Section: Porcine Kobuvirus (Pkv) Was First Identified In 2008 Inmentioning
confidence: 99%
“…PKV is a non-enveloped, singlestranded, positive-sense RNA virus that was fi rst detected in Hungary in early 2007 (Reuter et al, 2008), and has now been detected worldwide (Khamrin et al, 2010;Sisay et al, 2013;Yu et al, 2009). While the pathogenesis of PKV is relatively unknown, Park et al suggested that PKV could be the etiological agent of gastroenteritis in pigs based on statistical analysis (Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%